Early discharge planning in preterm low birth weight babies: A quality improvement project. (June 2017) - Anand, Amudha Jayanthi; Chua, Mei Chien; Khoo, Siok Hong; Yuen, Poh Leng; Fong, Mary Choi Wan; Goh, Annie; Agarwal, Pratibha
Introduction: Extended hospitalization of low birth weight infants increases risk of medical and psychosocial complications. Our aim was to reduce the length of hospitalization and assess safety and cost savings of discharging infants at a weight of 1900 g instead of 2000 g, as has been the practice. Methods: This is a single-centre, nurse led quality improvement project done at a tertiary neonatal unit in Singapore with primary outcome of reducing average length of stay in selected low birth weight infants. In phase 1, infants with birth weight between 1000 and 1700 g were discharged at 1900 g, provided they met the discharge criteria. Interventions were introduced in phase 2 after interim analysis for the two most common causes for delayed discharge: poor bottling skills and waiting time for scheduled herniotomy. Results: In phase 1, the mean hospitalization stay was reduced by 5.5 days, with 21% of the babies discharged at 1900 g. The safety of the intervention was assessed by rehospitalization rates, and found to be negligible. Interventions introduced in phase 2 to address the two major causes of delayed discharge did not improve the outcome. The estimated cost savings for each subsidized patient after implementation of the interventions was S$340–1100 over the two phases. Conclusion: Though only 21% of eligible infants could be discharged early, the study helped us identify key areas of intervention to facilitate early discharge of preterm infants. These included improving babies' sucking skills, planning for early surgery, and providing adequate parental training. Safety and cost savings appear to be promising as well.